2018
DOI: 10.1002/jcp.26589
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19 mediates LCoR to impact the osteogenic and adipogenic differentiation of mBMSCs in mice through sponging miR‐188

Abstract: The research aimed to examine the expression of lncRNA H19, miR-188, and LCoR in mouse bone marrow stromal stem cells (mBMSCs), and to investigate the regulatory mechanism of lncRNA H19/miR-188/LCoR in osteogenic and adipogenic differentiation of mBMSCs. The expression of miR-188 in mBMSCs and osteogenesis induced mBMSCs was detected by stem-loop RT-PCR, while the expression of H19 and LCoR in mBMSCs and adipogenesis induced mBMSCs was examined by qRT-PCR. Luciferase reporter assay verified the targeted relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
(42 reference statements)
1
46
0
Order By: Relevance
“…Subconfluent mouse hepatocyte iHPx cells were infected with Ad-H19, Ad-siH19, Ad-siMlxipl, Ad-H19 + Ad-siMlxip or Ad-RFP for 36 h. The infected hepatocytes were collected and subcutaneously injected into the flanks of athymic nude mice for 10 d. Masses at the injection sites were retrieved, fixed and snap-frozen or paraffin embedded. 52,53 Furthermore, H19 was shown to promote skeletal muscle insulin sensitivity by targeting AMPK. B, Frozen sections were subjected to ORO staining.…”
Section: Discussionmentioning
confidence: 99%
“…Subconfluent mouse hepatocyte iHPx cells were infected with Ad-H19, Ad-siH19, Ad-siMlxipl, Ad-H19 + Ad-siMlxip or Ad-RFP for 36 h. The infected hepatocytes were collected and subcutaneously injected into the flanks of athymic nude mice for 10 d. Masses at the injection sites were retrieved, fixed and snap-frozen or paraffin embedded. 52,53 Furthermore, H19 was shown to promote skeletal muscle insulin sensitivity by targeting AMPK. B, Frozen sections were subjected to ORO staining.…”
Section: Discussionmentioning
confidence: 99%
“…In malignant tumors, it is well known that H19 is aberrantly expressed and regulates cell proliferation, migration, invasions, antiapoptosis, etc., as well as acts as a microRNA sponge to indirectly regulate the expression of microRNA target genes (Ye et al, 2019). Wang et al (2018a) have described that the lncRNA H19 and Liganddependent co-repressor (LCoR) were upregulated in mBMSCs under osteogenic induction, and miR-188 was downregulated, which regulated LCoR in mBMSCs. Subsequent investigation has elucidated that, when H19 was silenced, the levels of miR-188 were increased, leading to reduced osteogenic differentiation in mBMSCs (Wang et al, 2018a).…”
Section: Lncrna Involved In Bmsc Regulation Through Mirnamentioning
confidence: 99%
“…LncRNA binds to mRNA and inhibits its translation. (Huang et al, 2016;Wang et al, 2018) HoxA-AS3 (Xu et al, 2010;Liu et al, 2014aLiu et al, , 2014b (Zhang et al, 2018) 1 ADSCs = adipose-derived stem cells; BMSCs = bone-marrow derived mesenchymal stem cells; SVs = stromal vascular cells; C/EBPα = CCAAT/enhancer-binding protein alpha; HDAC = histone deacetylase; LCoR = ligand-dependent corepressor; ceRNA = competing endogenous RNA; EZH2 = enhancer of zeste 2; H3K27me3 = H3 lysine-27 trimethylation; Runx2 = runt-related transcription factor 2; FABP4 = fatty acid binding protein 4; GILZ = glucocorticoid-induced leucine zipper; CTGF = connective tissue growth factor; PTEN = phosphatase and tensin homolog; PPARγ = peroxisome proliferatoractivated receptor gamma; hnRNPU = heterogeneous nuclear ribonucleoprotein U; SIRT1 = Sirtuin 1; AdipoQ = adiponectin; RBM14 = RNA binding motif protein 14. Table 1.…”
Section: An Overview Of Lncrnasmentioning
confidence: 99%
“…The differentiation of MSC is regulated by intricate signaling pathways and epigenetic events, determining the specific lineage and phenotype (Augello and De Bari, 2010). Recent studies revealed that lncRNA ADINR (Xiao et al, 2015), HoxA-AS3 (Zhu et al, 2016), MIR31HG (Huang et al, 2017b), TINCR (Liu et al, 2018d), and Plnc1 (Zhu et al, 2018) favor adipogenic commitment, whereas H19 (Huang et al, 2016;Wang et al, 2018), MEG3 (Li et al, 2017), TCONS_00041960 (Shang et al, 2018), and GAS5 (Li et al, 2018;Liu et al, 2018a) suppress adipocyte determination, playing key roles in the determining molecular switch between adipocyte and other mesenchymal cell types.…”
Section: Lncrnas In Adipogenic Determinationmentioning
confidence: 99%
See 1 more Smart Citation